Characterization of commercial vehicles' start-up operations from in-use data. (February 2021) - Zhang, Chen; Miller, Eric; Kotz, Andrew; Kelly, Kenneth; Thornton, Matthew; Geller, Michael; Brezny, Rasto
Highlights: Commercial vehicles' start operation is characterized using extensive on-road data. Vehicle cold-start emissions would be influenced substantially by vehicle vocation. On-road data shows significant NOx can still be produced while engine is hot. The FTP cycle's representativeness is validated through real-world in-use data. Abstract: Diesel engines produce disproportionate levels of emissions when the engine and after-treatment systems are operating at low temperatures. This situation arises most commonly when the vehicle is first started after overnight. To quantify emissions attributable to vehicle starts, a sizable collection of on-road commercial vehicle operating data is analyzed to identify start-up events and inspect associated emissions. Data was obtained from the National Renewable Energy Laboratory's (NREL's) Fleet DNA and from the Center for Environmental Research & Technology (CE-CERT). Included are 500 + diesel vehicles with more than 42, 000 recorded days, drawn from 25 vocational categories across the United States. Analysis shows that vehicle behavior, in terms of engine cold- and warm-operation, starts per day, soak time, and warm-up duration, differs significantly between vehicle vocations. Also, weighting factors for cold- and hot-starts currently used in the U.S. Environmental Protection Agency's Federal Test Procedure (FTP) for heavy-duty emissions certification accurately represent real-world operations. Although the FTP includes a comparable fraction of cold operation, the hot fraction is much shorter than real-world operation due to limited test duration. The investigation also revealed that real-world engines operate for a significant amount of time when the engine coolant is in the "hot-stabilized" region, but the selective catalytic reduction (SCR) temperature is below its effective operating temperature of 200 °C. Of the vehicles under investigation, almost 20% of their operational time is within this condition. Thus, novel approaches to raise and maintain SCR temperature are highly required to further reduce engine emissions.